2020
DOI: 10.3892/mmr.2020.11211
|View full text |Cite
|
Sign up to set email alerts
|

Siva‑1 regulates multidrug resistance of gastric cancer by targeting MDR1 and MRP1 via the NF‑κB pathway

Abstract: Siva-1 is a well-known anti-apoptosis protein that serves a role in multiple types of cancer cells. However, whether Siva-1 affects multidrug resistance via the nF-κB pathway in gastric cancer is currently unknown. The present study aimed to determine the possible involvement of Siva-1 in gastric cancer anticancer drug resistance in vitro. a vincristine (Vcr)-resistant KaTo iii/Vcr gastric cancer cell line with stable Siva-1 overexpression was established. The protein expression levels of Siva-1, nF-κB, multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…It is therefore urgent to design chemotherapeutics that can evade or reverse MDR. Studies have analyzed MDR1 and MRP1 gene regulation by over-expressing Siva-1 and subsequently upregulating NF-κB in gastric cancer cell lines [5]. The aim of the present study was to further clarify the influences of Siva-1 on the mechanisms of cellular resistance to chemotherapy as well as the mechanisms of action in novel potential anticancer agents, which have been designed to overcome the resistance mechanisms.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It is therefore urgent to design chemotherapeutics that can evade or reverse MDR. Studies have analyzed MDR1 and MRP1 gene regulation by over-expressing Siva-1 and subsequently upregulating NF-κB in gastric cancer cell lines [5]. The aim of the present study was to further clarify the influences of Siva-1 on the mechanisms of cellular resistance to chemotherapy as well as the mechanisms of action in novel potential anticancer agents, which have been designed to overcome the resistance mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…Recombinant lentiviral vector for Siva-1 gene (LV-Siva-1-RNAi) and null vector (Lv-NC), purchased from the Shanghai Cancer Institute (Shanghai, China), were used to construct the Siva-1-downregulation lentivirus. The methods of LV-Siva-1-RNAi and transfection of MKN-28/VCR gastric cancer cells with LV-Siva-1-RNAi have been previously described [5]. MKN-28/VCR cells were seeded in 6-well plates with antibiotic-free medium.…”
Section: Gene Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…MDR1 and MRP1 are multi-drug resistant proteins, and their expressions can reflect the sensitivity of tumor cells to chemotherapy drugs ( 29 ). A previous study has shown that compared with CD133(−) glioblastoma stem cells, the protein expressions of MDR1 and MRP1 in CD133(+) cells are significantly increased ( 16 ).…”
Section: Discussionmentioning
confidence: 99%